History and Progress of Barley Breeding in Sládkovičovo - Psota, Vratislav; Krajčovič, Tomáš; Križanová, Klára; Sachambula, Lenka (KVASNY PRUMYSL, 2017)
Study summarizes the results of agronomical and malting parameters of spring malting barley varieties bred in the Breeding Station Sládkovičovo in the period of 1938–2010. Progress in breeding was refl ected in the year-on-year increase in grain yield by 0.024 t/ha, thousand grain weight by 0.07 g, sieving fractions above 2.5 mm by 0.14 percentage points (pp), further, year-on-year reduction in plant height by 0.18 cm and nitrogenous substances content by 0.03 pp were recorded. Year-on-year increase in extract content by 0.055 pp, apparent fi nal attenuation by 0.07 pp, Kolbach index by 0.11 pp and relative extract by 0.09 pp were identifi ed. The year-on-year decline in β-glucan content in wort by 5.4 mg/l and increase in the value of friability by 0.3 pp were recorded. Wort color and wort color after boiling increased year-on-year by 0.008 unit EBC and by 0.014 unit EBC.